Effects of sennosides on cellular electric activities in smooth muscle cells of guinea pig taenia coli - Yang Wen-Xiu; Jin Zheng-Gen; Xu Wen-Sheng; Tian Zai-Shan; Guo Shi-Duo (Acta Pharmacologica Sinica, 2016)
The effects of sennosides (Sen, an extract of Chinese rhubarb) on cellular spontaneous electric activities of guinea pig taenia coli were studied by intracellular microelectrode technique. Sen 0.1-20 mmol.L-1 improved the depolarization of cell membrane, quickened the burst of slow wave potential, and increased notably the frequency of spike potentials. Sen (20 mmol.L-1) induced spontaneous spike potentials. These results provide direct evidence for the enhancing effect of Sen on intestinal peristalsis at cellular level.